(untitled) - Proctor, Robert (London, 1988)
The book presents the most comprehensive account to date of Germany medical involvement in the sterilization and castration laws, the laws banning marriage between Jews and non-Jews, and the massive program to destroy "lives not worth living". the book demonstrates that the common picture of a passive scientific community coerced into cooperation with the Naziz fails to graps the reality of what actually happened - namely, that many of the political initiatives of the Naziz arose from within the scientific community, and that medical scientists actively designed and administrated key elements of National Socialist policy
Keywords: antisemitism,medecine,national socialism,physicians; political aspects,germany,political activity; germany,germany